A Thematic Review on Mathematical Model for Convective Boundary Layer Flow - Siti Farah Haryatie, Mohd Kanafiah; Abdul Rahman, Mohd Kasim; Syazwani, Zokri; Nur Syamilah, Arifin (Akademi Baru, 2021)
Convection refers to the heat transfer that occurs between moving fluid and surface at a different temperature. Nowadays, there has been a great deal of interest in the convective boundary layer fluid flow problems. Despite its popularity, the review paper discussing the mathematical model for various fluid types regarding various geometry and boundary conditions has been observed to fall short. This review paper adopts a thematic review based on the mathematical model captured in published fluid flow problems from 2015 until 2020. The articles were analysed using thematic analysis ATLAS.ti 8 software. Using keyword search and filtering criteria from Scopus and Web of Science (WOS) databases, 198 peer-reviewed journal articles were identified. However, after the exclusion and inclusion processes, only 50 articles were reviewed as final articles. The thematic review of these articles has further identified 120 initial codes characterising the mathematical model, grouped into 7 clusters: Viscoelastic, Williamson, Casson, Brinkman, Jeffrey, Nanofluid and hybrid Nanofluid. The report from the code-to-document in ATLAS.ti 8 found that the boundary condition, geometry and method were highlighted in the literature. The outcomes of this study will benefit the future research direction to identify the gap for future studies, specifically in extending the mathematical model for fluid flow problems as well as choosing the suitable geometry and boundary condition.